The role of tissue-resident memory T cells in immunity to Bordetella pertussis - Curham, Lucy (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2022)
Whooping cough (pertussis) is a severe respiratory disease cause by the Gram-negative bacterium Bordetella pertussis. Despite high vaccine coverage, a resurgence of pertussis has been observed over recent years. Although current acellular pertussis vaccines protect against severe disease, they do not induce sterilising immunity in the nasal cavity and this may contribute to asymptotic transmission of B. pertussis. Therefore, a better understanding of the mechanisms of protective immunity against B. pertussis in the nasal cavity is required to help inform the design of next generation pertussis vaccines. The results of this study found that CD4 tissue-resident memory T (TRM) cells, a population of memory T cells that express CD69 with or without CD103, accumulate and persist in the nasal mucosa of mice following B. pertussis infection. CD4 TRM cells were a major source of IL-17A in the nasal cavity. Furthermore, CD4 TRM cells expanded locally during re-challenge and this was associated with rapid clearance of the secondary infection with B. pertussis from the nasal cavity. Protection against primary and secondary infection of the nasal cavity with B. pertussis was lost in IL-17-/- mice and in mice depleted of CD4 T cells. Expansion of IL-17A-producing CD4 TRM cells was accompanied by the infiltration of a novel neutrophil population expressing Siglec-F, which exhibited high NETosis capacity. Accumulation of Siglec-F+ neutrophils was reduced in IL-17-/- mice and mice depleted of CD4 T cells. CXCL1, a chemokine required for neutrophil recruitment, was decreased in the nasal cavity of IL-17-/- mice, whereas intranasal IL-17A administration induced CXCL1 production in the nasal cavity. Furthermore, depletion of neutrophils significantly curtailed bacterial clearance from the nasal cavity during infection with B. pertussis. This study also revealed that respiratory CD4 TRM cells induced by natural infection or immunisation with a whole cell pertussis (wP) vaccine can produce IL-17A in the absence of TCR activation. CD4 TRM cells could be activated directly by the cytokines IL-23 with IL-1β or IL-18 or when cultured with innate immune cells stimulated with PAMPs or the unrelated pathogen Klebsiella pneumoniae. Furthermore, immunisation of mice with a wP vaccine conferred non-specific protection against K. pneumoniae infection of the nasal cavity. These findings demonstrated that CD4 TRM cells are a major source of protective IL-17A in the nasal cavity and can be maintained by non-specific activation, probably by unrelated pathogens, and should be considered when informing future immunisation strategies to control the transmission of B. pertussis in humans.
APPROVED